Increased serum asymmetric dimethylarginine level is an independent predictor of contrast-induced nephropathy - Özgür Günebakmaz; Mustafa Duran; Ekrem Karakaya; Esen Tanrıkulu; Mahmut Akpek; Ali Ergin; Mehmet Güngör Kaya (KARE Publishing, 2013)
Objectives: The aim of our study was to evaluate whether serum asymmetric dimethylarginine (ADMA) level is an independent predictor of contrast-induced nephropathy (CIN). Study design: The study involved 90 consecutive patients with stable angina pectoris who underwent coronary angiography and ventriculography. Baseline serum creatinine (SCr) levels ranged between ≥1.2 and <2 mg/dl. All patients were hydrated with intravenous isotonic saline at a rate of 1 ml/kg per hour for 6 hours before and 12 hours after the procedure. The primary end point was the occurrence of CIN. The secondary end point was the change in SCr levels at day 2 after the contrast exposure. Serum ADMA was determined by the ELISA method. Results: The CIN rate was 11.1%. We detected a statistically significantly higher serum ADMA level in the CIN(+) group compared to that of the CIN(-) group [210.6 ng/ml (115.6-217.2) vs. 91.5 ng/ml (65.2-122.1), p=0.01]. Mehran risk score and diabetes mellitus (DM) ratio were higher in the CIN(+) group compared to those values in the CIN(-) group [8 (5.75-10) vs. 5 (5-7), p=0.01 and 70% vs. 26.3%, p=0.01, respectively]. Serum ADMA level, Mehran risk score and DM were independent predictors of CIN (odds ratio (OR) 1.030, 95% confidence interval (CI) 1.011-1.050, p=0.002; OR 1.565, 95% CI 1.102- 2.223, p=0.012; OR 9.422, 95% CI 1.441-61.598, p=0.019, respectively). A serum ADMA level of >124.7 ng/ml had 80% sensitivity and 76% specificity in predicting the development of CIN. In addition, we found a positive correlation between SCr change and serum ADMA level (p=0.001, r=0.35). Conclusion: Our study demonstrates that increased serum ADMA level is an independent predictor of CIN.